2014
DOI: 10.1186/1471-2458-14-544
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular medication utilization and adherence among adults living in rural and urban areas: a systematic review and meta-analysis

Abstract: BackgroundRural residents face numerous barriers to healthcare access and studies suggest poorer health outcomes for rural patients. Therefore we undertook a systematic review to determine if cardiovascular medication utilization and adherence patterns differ for rural versus urban patients.MethodsA comprehensive search of major electronic datasets was undertaken for controlled clinical trials and observational studies comparing utilization or adherence to cardiovascular medications in rural versus urban adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 71 publications
(203 reference statements)
3
18
0
Order By: Relevance
“…The disparities were greater for LDL cholesterol, use of aspirin and use of statin therapy. These findings are consistent with other studies demonstrating suboptimum risk factor management in secondary CVD and stroke prevention populations, where rates of blood pressure control and use of antihypertensive agents range from 60 to 80% in developed countries, but can be as low as 13% in low-income countries [5,16,17]. For PAD, poor recognition of PAD as a marker for CV disease involving coronary, cerebral and renal vascular beds and conferring a mortality risk approximately equal to that of other manifestations of CV disease has been documented, as has poor adherence to treatment recommendations [18][19][20][21].…”
Section: Discussionsupporting
confidence: 92%
“…The disparities were greater for LDL cholesterol, use of aspirin and use of statin therapy. These findings are consistent with other studies demonstrating suboptimum risk factor management in secondary CVD and stroke prevention populations, where rates of blood pressure control and use of antihypertensive agents range from 60 to 80% in developed countries, but can be as low as 13% in low-income countries [5,16,17]. For PAD, poor recognition of PAD as a marker for CV disease involving coronary, cerebral and renal vascular beds and conferring a mortality risk approximately equal to that of other manifestations of CV disease has been documented, as has poor adherence to treatment recommendations [18][19][20][21].…”
Section: Discussionsupporting
confidence: 92%
“…The same finding was observed in a systematic review and meta-analysis [33]. A retrospective cohort study conducted in Canada also noted that there was no difference in drug adherence between urban and rural residents [34].…”
Section: Discussionsupporting
confidence: 75%
“…In fact, the study was limited to the country's capital. However, although the study was only conducted in an urban area, it may be assumed that these results may not differ significantly from rural areas, as one meta-analysis suggested that the environmental setting had no impact on adherence to cardiovascular and diabetes medication [40]. The participation rate of the pharmacies was very low, albeit in line with other national studies undertaken in recent years, and could be attributed to pharmacists' low motivation to participate in research studies [41].…”
Section: Discussionmentioning
confidence: 99%